ISLAM DAN BUDAYA LOKAL Studi terhadap Pemahaman, Keyakinan, dan Praktik Keberagamaan Masyarakat Batak Angkola di Padangsidimpuan Perspektif Antropologi - Sumper Mulia Harahap (Lembaga penelitian dan pengabdian kepada masyrakat, 2015)
Ritual is an expression of the religious ceremony system that reflect the relationship between human and spiritual nature. For user or participants, the ritual has an important social function, namely to integrate individuals in the community and to become instruments tend to channel negative energy. In the context of Islam, elements in Panaek Bungkulan scent mystical and superstitious deem incompatible with Sharia rules need to be eliminated, but for the elements of the other during the ritual can still be communicated and do not damage the faith of course still be done. Penetration of religion in the perspective of Panaek Bungkulan does not necessarily all eliminate the ritual practices of Angkola Batak Padangsidimpuan society. Although people accept Islam as a faith, in addition to receiving the teachings of Islam as a faith, in addition to receiving the teachings of modern into building a house, they still do not lose local traditions as custom value in the middle of modern globalisation era. The relationship between Islam and local traditions has formed a new habitat called local Islamic traditions. Dialectic between Islam and culture puts religious and local ritual as a field of contestation; it is such as panaek bungkulan tradition. This tradition is a heritage tradition that has been known to the people of Angkola batak long before Islam entered the batak land